KOMBINASI EKSTRAK KULIT MANGGIS DENGAN EKSTRAK KELOPAK BUNGA DAN EKSTRAK SARANG SEMUT SEBAGAI PENURUN KADAR KOLESTEROL DAN TRIGLISERIDA PADA TIKUS PUTIH JANTAN - Anjar Mahardian Kusuma; Erza Genatrika; Rossy Faizah Nur Utami; Trisna Rohmiyati; Susanti Susanti (Faculty of Pharmacy, Universitas Gadjah Mada, 2016)
Hypercholesterolemia is a disease associated with high levels of cholesterol and LDL levels in the blood. Utilization of the commercial drugs can be given; however apart from the expensive price, adverse side effects might occur. It makes people choose alternative medication with herbal medicine through the use of natural materials. This study aimed to determine the effect of the combination of mangosteen peel extract-extract of roselle calyx and mangosteen peel extract-extract the ant nest plant as lowering cholesterol and triglyceride levels in male rats. The method used in this study was a laboratory experimental method using device posttest only control group design (simple experimental design). This study used 25 male rats of Wistar strain, divided into 5 groups; Group I: group without treatment, group II: control group solvent (NaCMC 1%), group III: positive control group (Simvastatin), Group IV: combination group mangosteen peel extract (200 mg / kg) - extract of roselle calyx (250 mg / kg), group V: group combination of mangosteen peel extract 200 mg / kg) - extract anthill (270 mg / kg). Induction of cholesterol in rats using quail egg yolk (10 ml / kg). The results showed that there was no significant difference in cholesterol and triglycerides between the combination of both extracts of mangosteen peel with a positive control (p<0,05).